ANALISIS DRAMATURGI PENAMPILAN ANIES BASWEDAN DALAM KAMPANYE PILGUB 2017 - Catur Priyadi (Jurnal Pustaka Komunikasi, 2018)
This research purpose to analyse Anies Baswedans performance in his campaign during Governor election 2017 in Indonesia. Anies known as Indonesian Intelectual figure and decide to involve in Indonesian Politics. Researcher interest in Aniess decision to involve in politics and to recognize his self, wheter during campaign or not.This research is Dramaturgi Analyst with interaction symbolic approach. Kind of research is qualitative. As a research, this only focused on Anies Baswedans appearance, while he was in the campaign. Data of this research is qualitative, where data has not numbers. All data were substansive that interprete with erudite references. The analyst data system that used in this research progress to identify Anies Baswedans appearance during his campaign in Governor election 2017. Identify Aniess appearance divided in two parts, front stage ( during campaign) and back stage (daily life). As the result, researcher conclude that Anies Baswedan managed his impression in front stage well. Even this research found some discrepancies between his front stage and back stage. This Discrepancy is the differences between Aniess Statements with his daily life.